The effect community of inquiry assisted by social media on problem-solving ability in education policy courses - Sutarum; Akhmad Qomaru Zaman; Yayuk Chayatun Machsunah Machsunah (PPPM STKIP PGRI Lamongan, 2021)
This study aims to determine the effect of the Community of Inquiry (CoI) model assisted by social media on problem-solving abilities. This type of research is a Quasi Experiment with a Non-Equivalent Control Group Design. As an Experiment Class is the Civics Education Study Program, the treatment of the CoI learning model is assisted by Social Media, and as the Control Class is the Economic Education Study Program with the treatment of the CoI learning model without assistance. The data were collected using the test technique and observation sheet and analyzed with a t-test at a significance level (α) = 0.05. A value of 3.585 was obtained that the equal variances were not assumed to have a sig. 0.001 is less than 0.05, so Ho is rejected, and Ha is accepted. Thus, there is a significant influence between the CoI learning model assisted by social media on problem-solving in educational policy courses.